(untitled) (Baghdad Science Journal, 2024)
Echinococcus granulosus sensu stricto possesses very similar strains G1 and G3. Mitochondrial genes from NADH dehydrogenase (NAD) family have prominent roles in the identification of very similar strains G1 and G3. Thus, the present study mainly aimed to characterize the whole NAD1 gene (from the start codon to the stop codon) of hydatids isolated from humans. Hydatids were surgically isolated from the livers of patients, who are from Basrah and Maysan provinces, at Al-Sadir Teaching Hospital in Basrah province, Iraq. Protoscoleces were aseptically isolated from hydatid cysts and were used to extract DNA. Specific primers were employed to amplify the total NAD1 gene. A consensus sequence of nucleotides was separately generated from Basrah and Maysan sample sequences. Each consensus sequence had 1038 bp and it contained a start codon GTG at residues 87- 89 and a stop codon TAA at residues 978 – 980. The present study results displayed that each deduced amino acid sequence, predicated from a consensus sequence of nucleotides, had 297 amino acids. Furthermore, bioinformatics analysis revealed that each deduced amino acid sequence included a residue isoleucine (I188). This residue is only retained in the NAD1 protein of the G1 strain. The current study results also showed a predicated structural model of Basrah and Maysan NAD1 proteins and both of which had very similar homology models and the important residue I188 was located in the α10 helix. In total, for the first time in Iraq, this study characterized the whole NAD1 genes of E. granulosus protoscoleces and confirmed these NAD1 genes belonging to the G1 sheep strain.